Pengaruh Ekspor Komoditas Utama terhadap Penyerapan Tenaga Kerja di Provinsi Kalimantan Selatan - Nahda Muzlena; Syahrituah Siregar (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This research analyzed the export of primary commodities on labor absorptionin the South Kalimantan Province. The amount of data used is 15 years, which can beused in the data processing. Data is processed using panel data regression analysis.The results are finding that the effect export of primary commodities has a significanteffect on labor absorption.